2017
DOI: 10.1148/radiol.2016160639
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma in Patients with Cirrhosis: Differentiation from Hepatocellular Carcinoma by Using Gadoxetic Acid–enhanced MR Imaging and Dynamic CT

Abstract: Purpose To determine the imaging features at gadoxetic acid-enhanced magnetic resonance (MR) imaging of intrahepatic cholangiocarcinoma (IHCC) in a cirrhotic liver, with an emphasis on the distinction between IHCC and hepatocellular carcinoma (HCC) and on the comparison of nodule enhancement patterns between MR imaging and computed tomography (CT). Materials and Methods The institutional review board approved this study and waived the requirement for informed consent. Gadoxetic acid-enhanced MR and CT images i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…The majority of the grade 3 and 4 toxicities (72%) were laboratory abnormalities, none led to drug discontinuation, and many were in patients who had abnormal baseline liver function tests or blood counts. Although some patients with ICC can have underlying cirrhosis, only 1 patient in this trial had a history of cirrhosis according to a review of the imaging and clinical histories of all patients. The rate of dose reductions (63%) was similar to the rate seen in a phase 3 trial in advanced renal cell carcinoma (62%) but was higher than the rate seen in a phase 3 trial in metastatic castrate‐resistant prostate cancer (33%) and a phase 2 trial in breast cancer (34%), all of which evaluated daily 60‐mg dosing.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the grade 3 and 4 toxicities (72%) were laboratory abnormalities, none led to drug discontinuation, and many were in patients who had abnormal baseline liver function tests or blood counts. Although some patients with ICC can have underlying cirrhosis, only 1 patient in this trial had a history of cirrhosis according to a review of the imaging and clinical histories of all patients. The rate of dose reductions (63%) was similar to the rate seen in a phase 3 trial in advanced renal cell carcinoma (62%) but was higher than the rate seen in a phase 3 trial in metastatic castrate‐resistant prostate cancer (33%) and a phase 2 trial in breast cancer (34%), all of which evaluated daily 60‐mg dosing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it cannot be excluded that some ICC were erroneously diagnosed as HCC by CT or MRI. In a retrospective study conducted between 2008 and 2014, Choi et al[24] found that 14.1% (11/78, approximately 1–2/year) ICCs showed wash in and washout dynamic pattern in CT, and this ratio is 19.2% (15/78, approximately 1–2/year) in MR. Therefore, there was not enough evidence to deny the value of CEUS and justify the use of CT or MR in the diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, hypointense signal in an observation during the TP does not translate to “washout” in the same way that hypointensity during the PVP or delayed phases with ECA would. Indeed, if hypointensity in the TP is considered “washout,” the imaging specificity for HCC decreases from 98–100% to 86–95% . Therefore LI‐RADS restricts assessment of “washout” with gadoxetate to the PVP in order to maintain a specificity rate as close to 100% as possible …”
Section: Potential Pitfalls Of Gadoxetate Mrimentioning
confidence: 99%